Marginal and internal adaptation of lithium disilicate partial restorations: A systematic review and meta-analysis - Natalia Almeida Bastos; Sandro Basso Bitencourt; Renan Figueiredo Carneiro; Brunna Mota Ferrairo; Samira Sandy Ferreira Strelhow; Daniela Micheline dos Santos; Juliana Fraga Soares Bombonatti (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this meta analysis was to evaluate the influence of the processing method on the marginal and internal gaps of lithium disilicate inlays/onlays. Settings and Design: A systematic literature review was conducted using the PubMed/Medline, Embase, Scopus, and Cochrane Library databases. This review was registered on the PROSPERO platform. Materials and Methods: The studies were selected according to the marginal and internal gaps of two different fabrication methods for lithium disilicate (milled and pressed). Statistical Analysis Used: The meta analysis was performed based on the Mantel-Haenszel and inverse variance methods, using the random effects model and a 95% confidence interval. Results: From all databases, 127 studies were identified. Four in vitro studies were included in the qualitative analysis and three in the meta analysis. Moreover, 197 restorations were evaluated (103 pressed and 94 milled). During the evaluation of only the internal gap, there was a statistically significant difference favoring the pressed technique (P = 0.002). There was no statistically significant difference in the analyses of the marginal gap (P = 0.530) and the total gap (P = 0.450). Conclusion: Both the techniques provided acceptable marginal and total gaps, although the pressed technique revealed a more favorable internal adaptation than the milled onlays/inlays.